Effects of stress-induced solid phase transformations on residual stress in laser cladding a Fe-Mn-Si-Cr-Ni alloy coating. (August 2020) - Tian, Jiayu; Xu, Peng; Liu, Qibin
Abstract: Since the traditional techniques for eliminating the residual stress are complicated process and high production cost, we attempt to reduce the residual stress generated in laser cladding a Fe-Mn-Si-Cr-Ni alloy coating through stress-induce solid phase transformation (SSPT). A 3D thermo-mechanical finite element model for stress-induced solid phase transformations was developed to research the influences of SSPT on stress evolution during laser cladding a Fe-Mn-Si-Cr-Ni alloy coating. In the simulation calculation, the evolution and distribution of stress under two conditions (with SSPT and without SSPT) were analyzed and compared. In the experiment, the phase component and microstructure of the coating were researched adopting XRD and TEM respectively. Calculated results show that SSPT significantly reduces the residual stress in transverse and longitudinal direction, obtaining a more accurate stress result. The experimental results show that the stress generated in laser cladding induces austenite to transform into martensite, releasing residual stress and obtaining low residual stress coating. The present work can provide an available method for the simulation of stress-strain changes caused by stress-induced solid phase transformation and a new idea for eliminating residual stress in laser processing. Graphical abstract: Unlabelled Image Highlights: Effects of stress-induced phase transformation on residual stress in laser cladding is discussed. An available method for simulating the stress-induced phase transformation in laser cladding is provided. Stress-induced phase transformation can effectively reduce the residual stress generated in laser cladding.